NK cell-derived exosomes enhance the anti-tumor effects against ovarian cancer by delivering cisplatin and reactivating NK cell functions - Luo, Heyong; Zhou, Yanhua; Zhang, Jing; Zhang, Yingchun; Long, Shiqi; Lin, Xiaojin; Yang, Anqing; Duan, Jiangyao; Yang, Na; Yang, Zhiru; Che, Qiyuan; Yang, Yuxin; et al. (Frontiers in Immunology, 2023)
Exosomes are membranous vesicles actively secreted by almost all cells and they deliver certain intracellular molecules, including nucleic acids, proteins, and lipids, to target cells. They are also considered to be good carriers for drug delivery due to their biocompatibility, high permeability, low immunogenicity, and low toxicity. Exosomes from immune cells were also reported to have immunomodulatory activities. Herein we evaluated the application of exosomes derived from expanded natural killer cells (eNK-EXO) for the treatment of ovarian cancer (OC). We demonstrate that eNK-EXO express typical protein markers of natural killer (NK) cells, can be preferentially uptaken by SKOV3 cells, and display cytotoxicity against OC cells. Furthermore, eNK-EXO loaded with cisplatin could sensitize drug-resistant OC cells to the anti-proliferation effect of cisplatin. In addition, we show that eNK-EXO could activate NK cells from immunosuppressive tumor microenvironment, the mechanism of which is explored by transcriptional analysis. In summary, eNK-EXO exhibit anti-tumor activity against OC on its own, could be used to deliver cisplatin and enhance its cytotoxic effect against drug-resistant OC cells and also reverse the immunosuppression of NK cells, which may lead to great prospect of using eNK-EXO in the treatment of OC in the clinic. Our work also builds a strong foundation for further evaluation of eNK-EXO in other solid tumor therapies.